Comparison of the effects of isoflurane and sevoflurane on surgical stress in intracranial tumor surgery - Muslu Erdem, Vuslat; Sayan, Halil Erkan; Korfali, Sefika Gulsen (The European Research Journal, 2021)
Objectives: Surgeries can trigger stress responses including metabolic and hormonal changes. It is important to suppress stress response during surgery. We compared the effects of isoflurane and sevoflurane on surgical stress in intracranial tumor surgery. Methods: Thirty ASA physical status I, II, III patients, scheduled for elective craniotomies, were enrolled in this prospective, randomized study. Anesthesia was induced with sodium thiopental fentanyl and vecuronium bromide and maintained with a 50% oxygen-air mixture along with isoflurane or sevoflurane. Venous blood was sampled to measure cortisol, ACTH and prolactin levels 24 hours before surgery, 1 min before anesthesia induction, during tumor removal, 1 min after extubation, at 3, 6, 12, 24, 48 hours. Results: There was no statistically significant difference between two groups regarding demographic characteristics of patients. In group I, ACTH levels were significantly higher 1 min after extubation, at 3 and 6 hours. In Group S, significant increases were observed during tumor removal, 1 min after extubation, at 3 and 6 hours. Cortisol levels were significantly higher in both group after tumor removal, 1 min after extubation, at 3, 6, 12 and 24 hours. Prolactin levels were significantly higher in Group I during tumor removal, after extubation, at 3 and 6 hours. In group S, significant increase in prolactin level was observed only during tumor removal and 1 min after extubation. There were no significant differences in ACTH, cortisol and prolactin values between the two groups. Conclusions: Using isoflurane or sevoflurane for anesthesia during intracranial tumor surgery are not superior to each other regarding hemodynamic and hormonal stress response.